Overlapping copyright and trademark protection: A call for concern and action - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2014)
Currently, many forms of intellectual property can qualify for protection both under trademark and copyright law. Granting trademark protection for these works has the potential to negatively impact the social bargain upon which copyright protection is built and justified. Over the past few decades several judicial decisions have recognized this overlapping protection; generally, however, the majority of courts have proved reluctant to comprehensively address the issue, and have consistently accepted that trademark protection can apply to creative works when they are used to identify products offered for sale in the market. This perceived judicial support has contributed to further overlapping protection and, in turn, an increase in trademark claims.